Spark plasma sintering Cu / MoAlB shell-imitating structure composite material and preparation method and application thereof
The preparation of Cu/MoAlB imitation shell structure composite material through discharge plasma sintering process solves the problem of easy damage to existing copper alloy track materials under high velocity and high current conditions, and achieves excellent conductivity, wear resistance, lubrication and mechanical properties. The service life of the electromagnetic track transmitting device has been extended.
Patent Information
- Application Number
- CN202410293765.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2025-02-18
AI Technical Summary
The existing copper alloy track materials are prone to damage under high velocity and high current conditions, and the high resistance of molybdenum leads to excessive heat, affecting the service life and efficiency of the electromagnetic track transmitter.
Cu/MoAlB imitation shell structure composite material is prepared by discharge plasma sintering technology, and a composite powder with MoAlB powder attached to sheet Cu powder is formed by high-energy ball milling and ultrasonic treatment, and a dense imitation shell structure is obtained through discharge plasma sintering technology.
It realizes excellent conductivity, wear resistance, lubricating performance and mechanical properties of composite materials, extends the service life of track materials of electromagnetic track transmitter devices, and is easy to manufacture on a large scale.
Smart Images

Figure CN119464813A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-based composite materials, and in particular relates to a spark plasma sintered Cu / MoAlB shell-like structure composite material and a preparation method and application thereof. Background Art
[0002] The electromagnetic rail launcher is a linear motor that converts the electrical energy of a pulse power source into the kinetic energy of a load. It has the advantages of high launch speed, short start-up time, large launch kinetic energy, and variable load. It has great potential advantages and broad application prospects in both military and civilian fields. For example, the electromagnetic rail gun is a new concept kinetic weapon that uses electromagnetic energy to drive the armature with current to slide to ultra-high speed. Compared with conventional artillery, it has the advantages of high initial velocity, great power, high safety, strong controllability, simple operation, and high cost-effectiveness. It has great strategic and tactical application value in future wars.
[0003] The working principle of the electromagnetic rail launcher with a solid armature is that the armature is in direct contact with the two rails to conduct pulse current to excite the magnetic field, and the armature is pushed by the electromagnetic force to accelerate the load for launch. Due to the characteristics of large current, strong magnetic field, high load, high relative speed, high temperature, high contact pressure, etc., the armature-rail contact pair has considerable damage. Among them, the rail is a core component that is repeatedly used in the electromagnetic rail launcher. Its surface morphology is closely related to the contact state of the armature and rail, and is related to the efficiency, stability and safety of electromagnetic launch. Its damage will reduce the number of times the rail launcher is used and limit its strategic advantage. In order to ensure the launch accuracy, service life and energy utilization of the electromagnetic rail device, the breakthrough of rail materials has become one of the key technologies of the electromagnetic rail launcher.
[0004] Copper alloys have become an ideal material for electromagnetic rails due to their high electrical and thermal conductivity. However, the hardness and strength of copper alloys have not been sufficient to withstand the ultra-high speed between the rails and the armatures, and are prone to surface damage such as planing and sliding. Experiments have shown that copper alloy rails do not suffer from severe ablation and wear in low-speed, high-current plasma armatures, but they are very obvious in solid armatures and hybrid armatures. Although molybdenum can significantly improve the rail's anti-ablation performance, its high resistance will cause the rail to generate excessive heat during operation, which is not conducive to the practical application and commercialization of electromagnetic rail launch devices. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a spark plasma sintered Cu / MoAlB shell-like structure composite material and its preparation method and application in view of the deficiencies in the above-mentioned prior art. By taking advantage of controllable performance, the composite material can play an excellent role in friction reduction, wear resistance and conductivity during service, and is used to solve the technical problems of poor physical properties and short service life of composite materials. The composite material can be suitable for track materials of electromagnetic track launch devices.
[0006] The present invention adopts the following technical solutions:
[0007] A method for preparing a Cu / MoAlB shell-like structure composite material by spark plasma sintering comprises the following steps: subjecting 80-95wt% of Cu powder and 5-20wt% of MoAlB powder to high-energy ball milling to obtain a Cu / MoAlB composite powder in which MoAlB powder is attached to the surface of flaky Cu powder; placing the Cu / MoAlB composite powder in anhydrous ethanol to perform ultrasonic treatment; and subjecting the Cu / MoAlB composite powder after the ultrasonic treatment to spark plasma sintering to obtain a Cu / MoAlB shell-like structure composite material.
[0008] Preferably, during the high-energy ball milling mixing process, the ball-to-material ratio is 20:1, the ball milling speed is 300-400 r / min, and the ball milling time is 1-2 h.
[0009] More preferably, the ball mill is a stainless steel ball mill, and the grinding balls are 1 mm and 5 mm stainless steel balls mixed in a ratio of 1:1.
[0010] Preferably, the Cu / MoAlB composite powder is placed in a graphite mold and then subjected to ultrasonic treatment in an anhydrous ethanol environment.
[0011] More preferably, graphite paper is placed in the graphite mold.
[0012] Preferably, the ultrasonic treatment time is 30 to 60 minutes.
[0013] Preferably, the heating rate of spark plasma sintering is 50-100° C. / min, the holding temperature is 900-950° C., the holding time is 10-20 min, and the pressure is 25-35 MPa.
[0014] Preferably, spark plasma sintering is performed in a vacuum environment.
[0015] Another technical solution of the present invention is a spark plasma sintered Cu / MoAlB shell-like structure composite material, the spark plasma sintered Cu / MoAlB shell-like structure composite material has a micro-Vickers hardness of 73.1-114.2 HV and a density of 91.5%-99.5%.
[0016] Another technical solution of the present invention is that the spark plasma sintered Cu / MoAlB shell-like structure composite material is applied to the track material of the electromagnetic track launch device.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects:
[0018] A method for preparing a Cu / MoAlB imitation shell structure composite material by spark plasma sintering, wherein Cu is 80-95wt% and MoAlB is 5-20wt%. The Cu / MoAlB imitation shell structure composite material can be ensured to have good lubrication, mechanical and electrical conductivity and meet required service conditions. By adopting a spark plasma sintering preparation process, an electromagnetic rail launch device track material with excellent electrical conductivity, wear resistance, lubrication and mechanical properties can be prepared, and large-scale manufacturing can be easily achieved, thereby providing a feasible preparation method for a technical breakthrough in the electromagnetic rail launch device track material.
[0019] Furthermore, the ball-to-material ratio of the ball-milled mixed powder is 20:1, the ball-milling speed is 300-400 r / min, and the ball-milling time is 1-2 h, which can transform the spherical Cu powder into flaky Cu powder, and make the MoAlB powder adhere to the flaky Cu powder, ensuring that the composite material organization can form a shell-like structure.
[0020] Furthermore, the grinding balls are 1 mm and 5 mm stainless steel balls mixed in a ratio of 1:1. The larger size of the grinding balls can provide greater grinding energy, and the smaller size of the grinding balls can provide a greater number of impacts, which is conducive to the uniform attachment of the MoAlB powder to the flaky Cu powder.
[0021] Furthermore, the Cu / MoAlB composite powder is placed in a mold and ultrasonically treated in an anhydrous ethanol environment. The tiny vibrations during the ultrasonic treatment can cause the Cu / MoAlB composite powder to spontaneously form a brick structure. The graphite mold containing the powder needs to be completely immersed in anhydrous ethanol to ensure that the Cu / MoAlB powder is prevented from oxidation during the ultrasonic process.
[0022] Furthermore, the inside of the graphite mold is padded with graphite paper, which can ensure that the powder will not leak during the ultrasonic process, reduce the difficulty of demoulding after sintering, and make the surface of the sample smooth.
[0023] Furthermore, the duration of ultrasonic treatment of the mold in anhydrous ethanol is 30 to 60 min, which can ensure that the Cu / MoAlB powder completely forms a brick structure.
[0024] Furthermore, the heating rate is 50-100°C / min, the sample is kept at 900-950°C for 10-20 minutes, and the pressure is 25-30Mpa, which can ensure that the sample is non-oxidized, has a dense structure, has excellent electrical conductivity, and guarantees friction reduction performance. The sample has no defects such as component segregation, cracks, pores, inclusions, oxides, etc., and has high strength and hardness. The spark plasma sintering process can improve production capacity and is conducive to automation.
[0025] Furthermore, spark plasma sintering is performed in a vacuum environment, which is convenient for reducing oxidation of metal components of the sample during the sintering process.
[0026] The invention provides a spark plasma sintered Cu / MoAlB shell-like structure composite material, which has good mechanical strength. The added MoAlB component can effectively reduce the friction coefficient and achieve a self-lubricating effect.
[0027] The present invention avoids defects and failures of the track material of the electromagnetic track launch device during service to a certain extent, has dense structure, excellent electrical conductivity, guaranteed friction reduction performance, the sample has no defects such as component segregation, cracks, pores, inclusions, oxides, etc., has high strength and hardness, and prepares track materials with excellent electrical conductivity, wear resistance, lubrication performance, and mechanical properties, and is easy to achieve large-scale manufacturing.
[0028] In summary, the method of the present invention is simple to prepare, and the prepared spark plasma sintered Cu / MoAlB shell-like structure composite material has excellent electrical conductivity, wear resistance, lubricity and mechanical properties.
[0029] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a high-magnification SEM photo of an example sample prepared by the method of the present invention;
[0031] Figure 2 This is a low-magnification SEM photograph of an example sample prepared by the method of the present invention;
[0032] Figure 3 This is an EDS photo of an example sample prepared by the method of the present invention;
[0033] Figure 4 This is a graph showing how the hardness of the material prepared by the method of the present invention varies with its composition. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0036] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0037] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0038] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0039] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0040] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0041] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0042] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0043] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0044] The present invention provides a spark plasma sintered Cu / MoAlB shell-like structure composite material and a preparation method thereof, which can avoid defects and failures of track materials of electromagnetic track launch devices during service, have dense organization, excellent electrical conductivity, guaranteed friction reduction performance, and the sample is free of defects such as component segregation, cracks, pores, inclusions, oxides, etc., and has high strength and hardness. Track materials with excellent electrical conductivity, wear resistance, lubrication performance, and mechanical properties can be prepared, and large-scale manufacturing can be easily achieved.
[0045] See also Figure 1 The present invention provides a method for preparing a Cu / MoAlB shell-like structure composite material by spark plasma sintering, comprising the following steps:
[0046] S1. Place Cu and MoAlB powders weighed in different proportions in a ball mill, and mix the powders until they are completely uniform;
[0047] The composition ratio of Cu and MoAlB powder is: Cu is 80-95wt%, MoAlB is 5-20wt%. The ball mill is a stainless steel ball mill, the grinding balls are 1mm and 5mm stainless steel balls mixed in a ratio of 1:1, the ball-to-material ratio in the ball mill is 20:1, the ball mill speed is 300-400r / min, and the ball milling time is 1-2h.
[0048] S2, taking the uniformly mixed Cu / MoAlB composite powder and putting it into a graphite mold;
[0049] The mold size is a graphite mold with a diameter of 25 to 44 mm, and graphite paper is padded inside the mold.
[0050] S3. Place the graphite mold filled with Cu / MoAlB composite powder into a beaker filled with anhydrous ethanol, immerse the graphite mold completely in the anhydrous ethanol, and perform ultrasonic treatment for 30 to 60 minutes.
[0051] S4. The ultrasonically treated graphite mold is subjected to spark plasma sintering to obtain a Cu / MoAlB shell-like structure composite material with a dense structure.
[0052] During the sintering process, a vacuum environment is maintained, the heating rate is 50-100°C / min, the sample is kept at 900-950°C, the pressure is 25-35 MPa, and the holding time is 10-20 min.
[0053] The invention discloses a spark plasma sintered Cu / MoAlB shell-like structure composite material, with a micro-Vickers hardness of 73.1-114.2 HV, a density of 91.5%-99.5%, good mechanical strength, and the added MoAlB component can effectively reduce the friction coefficient to achieve a self-lubricating effect.
[0054] The composite material prepared by the invention has excellent high-temperature wear resistance and can be suitable for track materials of electromagnetic track launch devices.
[0055] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] 1) placing Cu / MoAlB composite powders weighed in different proportions in a ball mill, and ball milling the mixed powders until they are completely uniform;
[0058] The composition ratio of the Cu / MoAlB composite powder is: Cu is 95wt%, MoAlB is 5wt%; the ball mill is a stainless steel ball mill, the grinding balls are 1mm and 5mm stainless steel balls mixed in a ratio of 1:1, the ball-to-material ratio in the ball mill is 20:1, the ball mill speed is 300r / min, and the ball mill time is 1h.
[0059] 2) taking the uniformly mixed Cu / MoAlB composite powder and placing it into a graphite mold for ultrasonic treatment;
[0060] The mold size is a graphite mold with a diameter of 25 mm, and the inside of the mold is padded with graphite paper. The graphite mold filled with powder is completely immersed in anhydrous ethanol and ultrasonically treated for 30 minutes.
[0061] 3) The ultrasonically treated graphite mold is subjected to spark plasma sintering to obtain a Cu / MoAlB shell-like structure composite material with a dense structure.
[0062] The sintering process was carried out in a vacuum environment with a heating rate of 50°C / min. The sample was kept at 900°C for 10 min.
[0063] The material prepared in Example 1 has a loose structure, low electrical conductivity, and excellent anti-friction and lubrication properties. The material wears greatly during the friction process, has a Vickers hardness of 74.5 HV, and a density of 91.5%.
[0064] Example 2
[0065] 1) placing Cu / MoAlB composite powders weighed in different proportions in a ball mill, and ball milling the mixed powders until they are completely uniform;
[0066] The composition ratio of the Cu / MoAlB composite powder is: Cu is 90wt%, MoAlB is 10wt%; the ball mill is a stainless steel ball mill, the grinding balls are 1mm and 5mm stainless steel balls mixed in a ratio of 1:1, the ball-to-material ratio in the ball mill is 20:1, the ball mill speed is 400r / min, and the ball mill time is 1h.
[0067] 2) taking the uniformly mixed Cu / MoAlB composite powder and placing it into a graphite mold for ultrasonic treatment;
[0068] The mold size is a graphite mold with a diameter of 30.6 mm, and the inside of the mold is padded with graphite paper. The graphite mold filled with powder is completely immersed in anhydrous ethanol and ultrasonically treated for 40 minutes.
[0069] 3) The ultrasonically treated graphite mold is subjected to spark plasma sintering to obtain a Cu / MoAlB shell-like structure composite material with a dense structure.
[0070] The sintering process was carried out in a vacuum environment with a heating rate of 50°C / min. The sample was kept at 900°C for 15 min.
[0071] The material prepared in Example 2 has a denser structure, higher electrical conductivity, and excellent mechanical properties. The wear during the wear process is relatively large, the Vickers hardness is 80.3 HV, and the density is 93.6%.
[0072] Example 3
[0073] 1) placing Cu / MoAlB composite powders weighed in different proportions in a ball mill, and ball milling the mixed powders until they are completely uniform;
[0074] The composition ratio of the Cu / MoAlB composite powder is: Cu is 85wt%, MoAlB is 15wt%; the ball mill is a stainless steel ball mill, the grinding balls are 1mm and 5mm stainless steel balls mixed in a ratio of 1:1, the ball-to-material ratio in the ball mill is 20:1, the ball mill speed is 400r / min, and the ball mill time is 2h.
[0075] 2) taking the uniformly mixed Cu / MoAlB composite powder and placing it into a graphite mold for ultrasonic treatment;
[0076] The mold size is a graphite mold with a diameter of 30.6 mm, and the inside of the mold is padded with graphite paper. The graphite mold filled with powder is completely immersed in anhydrous ethanol and ultrasonically treated for 40 minutes.
[0077] 3) The ultrasonically treated graphite mold is subjected to spark plasma sintering to obtain a Cu / MoAlB shell-like structure composite material with a dense structure.
[0078] The sintering process was carried out in a vacuum environment with a heating rate of 50°C / min. The sample was kept at 900°C for 15 min.
[0079] The material prepared in Example 3 has a relatively dense organizational structure, high electrical conductivity, good anti-friction and lubrication properties, relatively small wear during the wear process, a Vickers hardness of 100.4 HV, and a density of 95.5%.
[0080] Example 4
[0081] 1) placing Cu / MoAlB composite powders weighed in different proportions in a ball mill, and ball milling the mixed powders until they are completely uniform;
[0082] The composition ratio of Cu / MoAlB composite powder is: Cu is 80wt%, MoAlB is 20wt%. The ball mill is a stainless steel ball mill, the grinding balls are 1mm and 5mm stainless steel balls mixed in a ratio of 1:1, the ball-to-material ratio in the ball mill is 20:1, the ball mill speed is 400r / min, and the ball milling time is 2h.
[0083] 2) taking the uniformly mixed Cu / MoAlB composite powder and placing it into a graphite mold for ultrasonic treatment;
[0084] The mold size is a graphite mold with a diameter of 44 mm, and the inside of the mold is padded with graphite paper. The graphite mold filled with powder is completely immersed in anhydrous ethanol and ultrasonically treated for 60 minutes.
[0085] 3) The ultrasonically treated graphite mold is subjected to spark plasma sintering to obtain a Cu / MoAlB shell-like structure composite material with a dense structure.
[0086] The sintering process was carried out in a vacuum environment with a heating rate of 50°C / min. The sample was kept at 950°C for 20 min.
[0087] The material prepared in Example 4 has a dense structure, low electrical conductivity, excellent anti-friction and lubrication properties, less material wear during the friction process, a Vickers hardness of 114 HV, and a density of 99.5%.
[0088] See also Figure 1 The high-magnification SEM photos of the example samples show the shell-like layered structure of the Cu / MoAlB composite material. This structure effectively balances the strain distribution, inhibits local severe deformation and sudden failure, and thus can maximize the comprehensive performance of the material.
[0089] See also Figure 2 The low-magnification SEM photos of the example samples show the overall shell-like structure of the Cu / MoAlB composite material, and the reinforced ceramic particles have an obvious layered distribution in the material, which is similar to the structure of shell materials.
[0090] See also Figure 3 , EDS photo of the example sample. The layered structural characteristics of the Cu / MoAlB shell-like structure composite material can be more clearly observed from the energy spectrum.
[0091] See also Figure 4 , the micro-Vickers hardness gradually decreases with the increase of copper content, and the performance of the composite material can be controlled by controlling the copper content.
[0092] In summary, the present invention provides a spark plasma sintered Cu / MoAlB shell-like structure composite material and a preparation method thereof. By adopting a spark plasma sintering preparation process, it is possible to prepare an electromagnetic gun track material with excellent electrical conductivity, wear resistance, lubrication and mechanical properties, and it is easy to achieve large-scale preparation, thus providing a feasible preparation method for a technological breakthrough in the track material of an electromagnetic track launch device.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a Cu / MoAlB shell-like structure composite material by spark plasma sintering, characterized in that: 80-95wt% of Cu powder and 5-20wt% of MoAlB powder are mixed by high-energy ball milling to obtain a Cu / MoAlB composite powder in which MoAlB powder is attached to the surface of flaky Cu powder; the Cu / MoAlB composite powder is placed in anhydrous ethanol for ultrasonic treatment; and the Cu / MoAlB composite powder after ultrasonic treatment is subjected to spark plasma sintering to obtain a Cu / MoAlB shell-like structure composite material.
2. The method for preparing the Cu / MoAlB shell-like structure composite material by spark plasma sintering according to claim 1, characterized in that: During the high-energy ball milling mixing process, the ball-to-material ratio is 20:1, the ball milling speed is 300-400 r / min, and the ball milling time is 1-2 h.
3. The method for preparing the Cu / MoAlB shell-like structure composite material by spark plasma sintering according to claim 2, characterized in that: The ball mill is a stainless steel ball mill, and the grinding balls are 1mm and 5mm stainless steel balls mixed in a ratio of 1:
1.
4. The method for preparing the Cu / MoAlB shell-like structure composite material by spark plasma sintering according to claim 1, characterized in that: The Cu / MoAlB composite powder was placed in a graphite mold and then ultrasonically treated in an anhydrous ethanol environment.
5. The method for preparing the Cu / MoAlB shell-like structure composite material by spark plasma sintering according to claim 4, characterized in that: Graphite paper is placed in the graphite mold.
6. The method for preparing the Cu / MoAlB shell-like structure composite material by spark plasma sintering according to claim 1, characterized in that: The ultrasonic treatment time is 30 to 60 minutes.
7. The method for preparing the Cu / MoAlB shell-like structure composite material by spark plasma sintering according to claim 1, characterized in that: The heating rate of spark plasma sintering is 50-100°C / min, the holding temperature is 900-950°C, the holding time is 10-20min, and the pressure is 25-35MPa.
8. The method for preparing the Cu / MoAlB shell-like structure composite material by spark plasma sintering according to claim 1, characterized in that: Spark plasma sintering is carried out in a vacuum environment.
9. A spark plasma sintered Cu / MoAlB shell-like structure composite material, characterized in that: The Cu / MoAlB shell-like structure composite material prepared by spark plasma sintering according to any one of claims 1 to 9 has a micro-Vickers hardness of 73.1 to 114.2 HV and a density of 91.5% to 99.5%.
10. The spark plasma sintered Cu / MoAlB shell-like structure composite material according to claim 9 is used as a track material for an electromagnetic track launch device.